Schools for All : The Blacks and Public Education in the South, 1865-1877 - Vaughn, William Preston (Book collections on Project MUSE., 1974)
Schools for All provides the first in-depth study of black education in Southern public schools and universities during the twelve-year Reconstruction period which followed the Civil War. In the antebellum South, the teaching of African Americans was sporadic and usually in contravention to state laws. During the war, Northern religious and philanthropic organizations initiated efforts to educate slaves. The army, and later the Freedmen's Bureau, became actively involved in freed-men's education. By 1870, however, a shortage of funds for the work forced the bureau to cease its work, at which.